2018
DOI: 10.1111/jcmm.14060
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from mesenchymal stem cells expressing miR‐125b inhibit neointimal hyperplasia via myosin IE

Abstract: Intercellular communication between mesenchymal stem cells (MSCs) and their target cells in the perivascular environment is modulated by exosomes derived from MSCs. However, the potential role of exosome‐mediated microRNA transfer in neointimal hyperplasia remains to be investigated. To evaluate the effects of MSC‐derived exosomes (MSC‐Exo) on neointimal hyperplasia, their effects upon vascular smooth muscle cell (VSMC) growth in vitro and neointimal hyperplasia in vivo were assessed in a model of balloon‐indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 59 publications
1
24
0
5
Order By: Relevance
“…They also characterized neural growth factor transcripts in rAMSC-EV (Bucan et al, 2019). Another study from Wang et al (2019) used DIO to label MSC-EV in a rat carotid artery balloon injury model. They found that MSC-EV can transfer miR−125b to vascular smooth muscle cells, which can attenuate neointimal formation and could be a therapeutic target of vascular diseases (Wang et al, 2019).…”
Section: Biodistribution and Targeting Of Msc-ev To Target Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also characterized neural growth factor transcripts in rAMSC-EV (Bucan et al, 2019). Another study from Wang et al (2019) used DIO to label MSC-EV in a rat carotid artery balloon injury model. They found that MSC-EV can transfer miR−125b to vascular smooth muscle cells, which can attenuate neointimal formation and could be a therapeutic target of vascular diseases (Wang et al, 2019).…”
Section: Biodistribution and Targeting Of Msc-ev To Target Tissuesmentioning
confidence: 99%
“…Another study from Wang et al (2019) used DIO to label MSC-EV in a rat carotid artery balloon injury model. They found that MSC-EV can transfer miR−125b to vascular smooth muscle cells, which can attenuate neointimal formation and could be a therapeutic target of vascular diseases (Wang et al, 2019). There are also several reports of labeling MSC-EV with different labeling agents such as DiI (1,1 -Dioctadecyl-3,3,3 ,3 -Tetramethylindocarbocyanine Perchlorate), Alexa fluor 488, and gadolinium for locating the biodistribution of EV (Abello et al, 2019;Chew et al, 2019;Cui et al, 2019).…”
Section: Biodistribution and Targeting Of Msc-ev To Target Tissuesmentioning
confidence: 99%
“…Tal et al reported that exosomes from miR-126-3p-overexpressing MSCs stimulated angiogenesis and collagen maturity in a diabetic rat model [156]. Exosomes from miR-125b-overexpressing MSCs were reported to repress Myo1e expression and suppress the proliferation and migration of vascular smooth muscle cells in vitro and in vivo, suppressing neointimal hyperplasia [163].…”
Section: Gene Overexpression To Improve the Function Of Msc-derived Ementioning
confidence: 99%
“…Регенераторный потенциал рассматривается также и при повреждении печени [25][26][27], лёгких [28,29], нервной ткани [30][31][32][33][34][35], кожных покровов [36,37] и микроциркуляторного русла [38]. Перспективными могут оказаться свойства везикул оказывать стимулирующие пролиферацию действия [39][40][41], угнетать воспаление [42][43][44], снижать оксидативный стресс [45].…”
Section: потенциальные цели терапевтического применения ввunclassified
“…Инфаркт миокарда [2][3][4][5][6][7][8][9][10] Крыса [2][3][4][5][6][7]9] По периферии инфаркта [2][3][4] в/в [5][6][7]9] Увеличение фракции выброса [3,5,6], уменьшение КСО ЛЖ [2,5,6] Подавление апоптоза [3-4, 6, 7-9] Индукция ангиогенеза [3][4][5] Уменьшение фиброза [7,9] Альтернативная поляризация макрофагов [7] Усиление АОС [9] Мышь [8,10] Интрамиокардиально [8,10] Подавление апоптоза [8] Уменьшение воспаления, альтернативная активация макрофагов [10] Оксидативный стресс [45] Крыса Инъекция в орган [45] Подавление апоптоза и стимуляция пролиферации [45] Баллон-индуцированное повреждение сосудов [39] Крыса в/в [39] Подавление пролиферации и миграции клеток, уменьшение экспресс...…”
Section: путь введения эффектunclassified